(untitled) (Research, Society and Development, 2024)
Changes in tooth color are a common concern among patients, who seek whiter teeth and a more harmonious smile. In response to this demand, various commercial options have emerged to meet these needs, with hydrogen peroxide-based bleaching gels being recommended due to their proven efficacy and safety. Hydrogen peroxide is an oxidative substance available in different concentrations and application forms, such as in-office bleaching and at-home bleaching. Despite its widespread use, questions about its efficacy and safety frequently arise. The aim of this study is to conduct a literature review on dental bleaching methods and their efficacy, highlighting and demystifying concepts previously considered limiting for the bleaching technique. For this purpose, the PUBMED/MEDLINE databases were consulted. The literature analyzed indicates that the bleaching method is safe and effective. Its mechanism of action involves the oxidation of chromophores and alteration of the dental surface, leading to the perception of brighter teeth. To achieve satisfactory results, lower concentrations of peroxide and the at-home technique are effective and present a lower risk of sensitivity. Additionally, there is no evidence to prove the efficacy of whitening toothpastes or the need for a pigment-free diet during the dental bleaching process.